Experimental Investigation on Heat Pump for Electric Vehicles with different Refrigerant Injection Compressors. (August 2015) - Qin, Fei; Xue, Qingfeng; Zhang, Guiying; Zou, Huiming; Tian, Changqing
Abstract: Poor heating performance and operating safety in low ambient temperature of Air Source Heat Pump (ASHP) for Electric Vehicles (EVs) limits the development of EVs in cold region, because of no engines wash heat to use and low efficiency of electric heating. ASHP with refrigerant injection is a potential method to reduce the battery power consumption by increasing the heating capacity and operating safety of ASHP system. In this paper, a test bench which can be switched between with refrigerant injection ASHP system and traditional ASHP system for EVs aiming at cold region is developed. In order to analyze the influence of refrigerant injection porthole shapes to system performance, two scroll compressors with different injection portholes are refitted from comment electric compressor. The experiment results show that the heating capacity of refrigerant injection system is raised up to 27% than that of the traditional system. The bigger area of injection portholes can and make help to increase the heating capacity when in-car inlet air temperature is higher. The research will also promote the industrialization and practicability of refrigerant injection system and EVs.